Kinerja Pelayanan Dinas Perpustakaan Dan Kearsipan Provinsi Sulawesi Selatan - Muh. Wahyudi Mokobombang (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted with the aim of knowing how the process of managing parking retributions in Makassar City, what are the obstacles experienced in its management so far, the mechanism of collection, deposit until it arrives at the acceptance process into PAD which leads to / is beneficial for the development of Makassar City. In the field of library and information services, the library provides library services in various fields of science such as social sciences, humanities, science and technology and many others. One of the areas of circulation that provides information services to the public, libraries are the places most visited by people who want to get information. In this way, service officers at this library are required to improve their performance in order to provide good quality service to the community. However, in reality the existing service structure at the South Sulawesi Province Library and Archives Service is not yet fully in line with what the community expects. Library development and empowerment has not been optimal and library services are also not satisfactory. The existing phenomenon is that the performance of employees and contract workers in providing services is not fully in line with what users and the public expect, so the quality of library services still needs to be improved. This research was conducted to determine the performance of library services at the South Sulawesi Province Library and Archives Service.